The diagnostic value of component-resolved diagnostics in peanut allergy in children attending a Regional Paediatric Allergology Clinic. Issue 1 (December 2016) - van Veen, Leonieke; Heron, Michiel; Batstra, Manou; van Haard, Paul; de Groot, Hans
Abstract Background To date, diagnosing food allergies in children still presents a diagnostic dilemma, leading to uncertainty concerning the definite diagnosis of peanut allergy, as well as to the need for strict diets and the potential need for adrenalin auto-injectors. This uncertainty in particular is thought to contribute to a lower quality of life. In the diagnostic process double-blind food challenges are considered the gold standard, but they are time-consuming as well as potentially hazardous. Other diagnostic tests have been extensively studied and among these component-resolved diagnostics appeared to present a promising alternative: Ara h2, a peanut storage protein in previous studies showed to have a significant predictive value. Methods Sixty-two out of 72 children, with suspected peanut allergy were analyzed using serum specific IgE and/or skin prick tests and specific IgE to several components of peanut (Ara h 1, 2, 3, 6, 8, 9). Subsequently, double-blind food challenges were performed. The correlation between the various diagnostic tests and the overall outcome of the double-blind food challenges were studied, in particular the severity of the reaction and the eliciting dose. Results The double-blind provocation with peanut was positive in 33 children (53 %). There was no relationship between the eliciting dose and the severity of the reaction. A statistically significant relationship was found between the skin prick test, specific IgE directed to peanut, Ara h 1, Ara h 2 or Ara h 6, and the outcome of the food challenge test, in terms of positive or negative (P  < .001). However, we did not find any relationship between sensitisation to peanut extract or the different allergen components and the severity of the reaction or the eliciting dose. There was no correlation between IgE directed to Ara h 3, Ara h 8, Ara h 9 and the clinical outcome of the food challenge. Conclusions This study shows that component-resolved diagnostics is not superior to specific IgE to peanut extract or to skin prick testing. At present, it cannot replace double-blind placebo-controlled food challenges for determination of the eliciting dose or the severity of the peanut allergy in our patient group.